Love sugar magic : a dash of trouble - Meriano, Anna; Ortega, Mirelle (New York, NY : Walden Pond Press, an imprint of HarperCollinsPublishers, 2018)
Wanting to be a part of her family's Dia de los Muertos preparations, Leonora sneaks out of school to discover her mother, aunt, and older sisters have been keeping a secret.
Keywords: Family secrets -- Juvenile fiction; Witches -- Juvenile fiction; Magic -- Juvenile fiction; Bakers and bakeries -- Juvenile fiction; Family secrets -- Juvenile fiction; Witches -- Juvenile fiction; Magic -- Juvenile fiction; Bakers and bakeries -- Juvenile fiction; Fantasy